(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
In this paper we reflect on the approach of memories applied to the analysis of representations of the past of indigenous communities in Santiago del Estero, Argentina. We start from the understanding that the large corpus of conceptual categories of memory studies presents some limitations for thinking about the "present pasts" of indigenous communities in general. In this sense, we consider it appropriate to revisit some epistemological assumptions of the paradigms of memory in order to reflect on our case/context, considering contributions from local and national research on the indigenous question in particular. We conclude that the limitations of these categories, far from being devalued, invite us to take epistemological precautions to refine the theoretical approach in order to broaden and complexify a highly versatile and constantly growing field of study. Likewise, we conclude that the case of Santiago del Estero presents specific historical/political characteristics that force us to consider social/native categories to generate new conceptualisations that are not found even in national research on indigenous memories.